In situ Os isotopes in abyssal peridotites bridge the isotopic gap between MORBs and their source mantle. - Alard, O; Luguet, A; Pearson, N; Griffin, W; Lorand, J; Gannoun, A; Burton, K; O'Reilly, S (2005)
Abyssal peridotites are assumed to represent the mantle residue of mid-ocean-ridge basalts (MORBs). However, the osmium isotopic compositions of abyssal peridotites and MORB do not appear to be in equilibrium, raising questions about the cogenetic relationship between those two reservoirs. However, the cause of this isotopic mismatch is mainly due to a drastic filtering of the data based on the possibility of osmium contamination by sea water. Here we present a detailed study of magmatic sulphides (the main carrier of osmium) in abyssal peridotites and show that the 187Os/188Os ratio of these sulphides is of primary mantle origin and can reach radiogenic values suggesting equilibrium with MORB. Thus, the effect of sea water on the osmium systematics of abyssal peridotites has been overestimated and consequently there is no true osmium isotopic gap between MORBs and abyssal peridotites.